Unraveling the Mechanisms of Light-induced Hemolysis by First Transition Metal Phthalocyanines - Franklin R. Vargas (Archives of Advances in Biosciences)
Introduction: Phthalocyanines are molecules that possess distinctive properties as a result of their structural composition. They have the capacity to act as catalysts in a variety of chemical reactions and demonstrate potential for use in photodynamic cancer therapy. For this purpose, the phthalocyanine molecule requires a metal ion that is capable of undergoing changes in state and binding to other molecules. Photohemolysis is a widely utilized in vitro test for evaluating the efficacy of phthalocyanines as photosensitizers. Its primary advantages include straightforward detection of the photohemolytic process through UV-VIS spectroscopy and insight into the phototoxic mechanisms that these molecules develop. This study aimed to evaluate how the central metal ion affects the photobiological behavior of phthalocyanines on human erythrocytes and the possible phototoxic mechanisms involved in the hemolysis process. Materials and Methods: Phthalocyanines with various central metals (Zn, Cu, Ni, Fe, Mn, Co) were synthesized via microwave irradiation. The phototoxicity of the compounds was evaluated through light-induced hemolysis using isolated human erythrocytes. The degree of cell damage was determined by measuring the absorbance of hemoglobin at 545 nm. The traditional spectrophotometric approach was employed to assess the kinetics of photohemolysis under white light irradiation. The rate of hemolysis was employed as a means of determining the extent of phototoxic damage. Radical scavengers were employed to elucidate the phototoxic mechanism (Type I or Type II) of the synthesized phthalocyanines. Results: The synthesized phthalocyanines demonstrated a range of photohemolytic activities against human erythrocytes. Zinc phthalocyanine (ZnPc) demonstrated the most pronounced effect, followed by iron (FePc), nickel (NiPc), and copper (CuPc) phthalocyanines. Conversely, cobalt (CoPc) and manganese (MnPc) phthalocyanines exhibited the least notable activity. It is likely that photohemolysis occurred via both type I and type II mechanisms, with ZnPc generating the most reactive oxygen species. Moreover, the interaction of ZnPc with erythrocyte membranes may contribute to its pronounced photohemolytic activity. The results of scavenger experiments indicate that ZnPc induces hemolysis primarily via type I radicals. Conclusion: ZnPc demonstrated the most pronounced hemolytic effect, attributable to its superior membrane interaction and efficient generation of free radicals via a type I mechanism. The role of singlet oxygen was found to be minor. These findings indicate the potential of ZnPc for photodynamic therapy due to its type I phototoxicity.